Analyzing pattern in requirement analysis phase / Mohd Haslily Mohd Hanafiah - Mohd Hanafiah, Mohd Haslily (2004)
This research is study about 'Analyzing Pattern In Requirement Analysis Phase'. Since the term pattern introduced in field of problem-solving discipline of Software Engineering, it create a body of literature to help software developers resolve recurring problems encoimtered throughout all of software development. However as a first layer, requirement analysis guide and drive the software developer the way of project development. The objective of this research is to find out what are problem occur during applying pattern, what characteristic of good pattern and what advantages of pattern used, during requirement analysis phase in project development. For data collection. Questionnaire acts as a primary source, while Library Search and On-Line Search act as a secondary source to support the primary source. The findings are produce base on the objective and how the objectives are relate with pattern.